Combined Effect of Fatty Diet and Cognitive Decline on Brain Metabolism, Food Intake, Body Weight, and Counteraction by Intranasal Insulin Therapy in 3×Tg Mice - Sanguinetti, Elena; Guzzardi, Maria Angela; Panetta, Daniele; Tripodi, Maria; De Sena, Vincenzo; Quaglierini, Mauro; Burchielli, Silvia; Salvadori, Piero A.; Iozzo, Patricia (Frontiers in Cellular Neuroscience, 2019)
Obesity and cognitive decline can occur in association. Brain dysmetabolism and insulin resistance might be common underlying traits. We aimed to examine the effect of high-fat diet (HFD) on cognitive decline, and of cognitive impairment on food intake and body-weight, and explore efficacy of chronic intranasal insulin (INI) therapy. We used control (C) and triple transgenic mice (3xTg, a model of Alzheimers’ pathology) to measure cerebral mass, glucose metabolism, and the metabolic response to acute intranasal insulin administration (cerebral insulin sensitivity). Y-Maze, positron emission-computed tomography, and histology were employed in 8 and 14-month-old mice, receiving normal diet (ND) or HFD. Chronic INI therapy was tested in an additional 3xTg-HFD group. The 3xTg groups overate, and had lower body-weight, but similar BMI, than diet-matched controls. Cognitive decline was progressive from HFD to 3xTg-ND to 3xTg-HFD. At 8 months, brain fasting glucose uptake was increased by C-HFD, and this effect was blunted in 3xTg-HFD mice, also showing brain insulin resistance. Brain mass was reduced in 3xTg mice at 14 months. Dentate gyrus dimensions paralleled cognitive findings. Chronic INI preserved cognition, dentate gyrus and metabolism, reducing food intake and body weight in 3xTg-HFD mice. Peripherally, leptin was suppressed and PAI-1 elevated in 3xTg mice, correlating inversely with cerebral glucose uptake. In conclusion, 3xTg background and HFD exert additive (genes*lifestyle) detriment to the brain, and cognitive dysfunction is accompanied by increased food intake in 3xTg mice. PAI-1 levels and leptin deficiency were identified as potential peripheral contributors. Chronic INI improved peripheral and central outcomes.